The Black Panther, Masculinity Barriers to Medical Care, and Colorectal Cancer Screening Intention Among Unscreened American Indian/Alaska Native, Black, and White Men - Brooks, Ellen; Islam, Jessica Y.; Perdue, David G.; Petersen, Ethan; Camacho-Rivera, Marlene; Kennedy, Carson; Rogers, Charles R. (Frontiers in Public Health, 2022)
Objective. To determine if masculinity barriers to medical care and the death from colorectal cancer (CRC) of actor Chadwick Boseman (The Black Panther) influenced CRC early-detection screening intent among unscreened American Indian/Alaska Native (AIAN) and Non-Hispanic-Black (Black) men compared with Non-Hispanic-White (White) men. Methods. Using a consumer-panel, we surveyed U.S. men aged 18–75 years (N=895) using the 24-item Masculinity Barriers to Medical Care (MBMC) scale. We calculated the median score to create binary exposures to evaluate associations with CRC screening intent and conducted multivariable logistic regression to evaluate independent associations stratified by race/ethnicity. Results. Overall, Black respondents were most likely to have a high MBMC score (55%) compared to White (44%) and AIAN (51%) men (p=0.043). AIAN men were least likely to report CRC screening intent (51.1%) compared with Black (68%) and White men (64%) (p<0.001). Black men who reported the recent death of Chadwick Boseman increased their awareness of CRC were more likely (78%) to report intention to screen for CRC compared to those who did not (56%) (p<0.001). Black men who exhibited more masculinity-related barriers to care were more likely to intend to screen for CRC (OR: 1.76, 95% CI:0.98-3.16) than their counterparts, as were Black men who reported no impact of Boseman’s death on their CRC awareness (aOR: 2.96, 95% CI:1.13-7.67). Conversely, among AIAN men, those who exhibited more masculinity-related barriers to care were less likely to have CRC screening intent (aOR: 0.47, 95% CI: 0.27-0.82) compared with their counterparts. Conclusions. Masculinity barriers to medical care play a significant role in intention to screen for CRC. While Black men were most likely to state that The Black Panther’s death increased their awareness of CRC, it did not appear to modify the role of masculine barriers in CRC screening intention as expected. Further research is warranted to better understand how masculine barriers combined with celebrity-driven health-promotion interventions influence the uptake of early-detection screening for CRC. Impact. Our study provides formative data to develop behavioral interventions focused on improving CRC screening completion among diverse men.